THE IMPORTANCE OF ADVANCING TECHNOLOGY BASED ON EDUCATIONAL INNOVATIONS IN VOCATIONAL SCHOOLS - Duraku, Fakete (E-Journal VFU, 2025)
Vocational schools have to develop such technology-based educational innovations that would shape the future workforce for better quality in education. This paper overviews how the integration of information technology into the curriculum transformed the vocational course while highlighting its potential to transform teaching-learning processes. The vocational schools need to develop technology-based educational innovations in the light of molding the future workforce with better quality education.This paper thus intends to outline an overview of how the integration of information technology within this curriculum has transformed the course and its transformation into teaching and learning processes. Therefore, the development of technology-based educational innovation in vocational school training for a future workforce will lead to improvements in the quality of education forthcoming. This paper provides an overview of how information technology integration into the curriculum has revolutionized the vocational course and is bound to alter how teaching and learning are carried out. The paper further underlines the possible role of ICT in the personalization of learning for individual students and in developing competencies of the 21st century. In some cases, such technology-driven ways of vocational education pay off even with better learning outcomes and result in very good preparation in the quite fast-changing labor market. Amongst others, it indicated how information and communication technology can at least partly provide an answer to adapting learning to the needs of students and enabling the competencies demanded from an inhabitant of the 21st century.The findings hint at a possible role of ICT in accommodating students with special learning needs and developing 21st-century competencies. One positive finding, however, is that more technology-driven vocational education approaches pay off not just in terms of learning outcomes per se but even in better preparations for a rather rapidly changing labor market.